Retrospective Evaluation of Patients Who Underwent Bronchoscopy in a Tertiary Pediatric Intensive Care Unit - Emrah Gün; Hacer Uçmak; Fevzi Kahveci; Edin Botan; Anar Gurbanov; Burak Balaban; Hasan Özen; Fulden Aycan; Gülçin Çıplak; Gizem Özcan; Fazılcan Zirek; Sümeyye Sözduyar; et al. (Journal of Pediatric Emergency and Intensive Care Medicine, 2023)

(untitled)
Introduction:This study aims to evaluate bronchoscopy’s indications and clinical results in patients who underwent bronchoscopy during their stay in the pediatric intensive care unit (PICU).Methods:This study was carried out retrospectively in PICU between April 2019, and October 2021. The diagnoses of the patients, the reasons for bronchoscopy, where and by whom bronchoscopy was performed, complications related to bronchoscopy, and the contribution of bronchoscopy to diagnosis and treatment were determined.Results:Thirty-seven patients underwent bronchoscopy. The median age was 20 (7-126) months. The children comprised 17 females (45.9%). We performed bronchoscopy in 17 (45.9%) patients in the PICU and in 20 (54.1%) patients in the operating room. Pediatric intensive care physicians, 13 (35.1%) performed fifteen (40.5%) of bronchoscopy procedures pediatric pulmonologists and 9 (24.3%) pediatric surgeons. Nine patients underwent rigid bronchoscopy, 28 patients underwent flexible bronchoscopy. The median bronchoscopy time was 10 minutes (7.5-15). Bronchomalacia was found in 5 of the patients and tracheomalacia in 2 of them. Three patients (8.1%) had extraluminal airway compression. Bronchoscopy was performed in six patients due to foreign body aspiration. In 13 patients, peak inspiratory pressure and positive end-expiratory pressure of mechanical ventilation were decreased after the bronchoscopy procedure. During the bronchoscopy procedure, desaturation showed in 19 patients, bleeding in 4 patients, bradycardia in 4 patients, and short-term cardiac arrest in 3 patients. Three patients with cardiac arrest were patients who underwent rigid bronchoscopy. The median PICU length of stay was 52 days. There were no bronchoscopy-related deaths, but 9 patients died due to their primary disease.Conclusion:Bronchoscopy is a method that can be performed in PICU, both at the bedside and the operating room, to identify pathological changes in the airway in critical patients and to remove foreign bodies and life-threatening plugs in the airway. Its use for emergency or diagnostic purposes is increasing in PICUs.